Fundus Bleeding - Sahebaan Sethi (TNOA Journal of Ophthalmic Science and Research, 2024)
Fundus bleeding, commonly known as retinal haemorrhage, is a significant ocular manifestation associated with various systemic and ocular conditions. This abstract provides a comprehensive overview of the pathogenesis, diagnosis and management strategies of fundus bleeding. The abstract begins by discussing the underlying pathophysiology of fundus bleeding, which involves the rupture of retinal blood vessels leading to the extravasation of blood into the retinal layers. It highlights the diverse aetiologies of retinal haemorrhage, including trauma, vascular diseases, hypertension, diabetes, blood dyscrasias and ocular conditions such as retinal vein occlusion and macular degeneration. The manuscript further delves into the diagnostic modalities used to assess fundus bleeding, including fundus examination, optical coherence tomography (OCT), fluorescein angiography (FA) and fundus photography. It emphasizes the importance of accurate diagnosis to identify the underlying cause and guide appropriate management. The management strategies for fundus bleeding are discussed, considering both the underlying aetiology and severity of the haemorrhage. This includes conservative approaches, such as observation and control of systemic risk factors, as well as specific interventions like antivascular endothelial growth factor (anti-VEGF) therapy, laser photocoagulation and vitrectomy. In conclusion, this abstract provides a comprehensive overview of the pathogenesis, diagnosis and management of fundus bleeding or retinal haemorrhage. It serves as a valuable resource for clinicians and researchers involved in the care of patients with retinal haemorrhage, aiding in the understanding of its multifactorial aetiology and guiding evidence-based management strategies for improved visual outcomes.